In Vitro and In Silico Analysis of the Antibacterial Activity of Bioactive Compounds Extracted from Pineapple Peel - Sadik, Wafa Mohammad; Abdullah, Iman Tajer; Alnajar, Lana Abed (UI Scholars Hub, 2026)
Antibiotic resistance is a critical global challenge that requires the discovery of alternative therapeutic agents. Plants -derived compounds, such as those found in Ananas comosus (pineapple)peel, offer promising antibacterial potential. This study aimed to evaluate the antibacterial activity of pineapple peel extract using both in vitro and in silico approaches. Ethanolic extracts of pineapple peel were fractionated using silica gel chromatography, and the resulting fractions were analyzed by GC-MS. Antibacterial activity was tested against Gram-positive and Gram-negative pathogens using the agar well diffusion method, and the inhibition zones were recorded. Molecular docking was performed to assess the interaction of identified compounds with the CoA-bound OdaA protein of Pseudomonas aeruginosa (PDB ID:7BOR). Fractions 3 and 4 exhibited the strongest antibacterial activity, producing inhibition zones up to 23 mm against P. aeruginosa at 50 mg/ml. GC-MS identified several bioactive compounds, among which 4-Methoxyphenylglyoxal hydrate showed the highest docking affinity (-5.56 Kcal/mole) and formed two hydrogen bonds with the bacterial target protein. These findings demonstrate that pineapple peel, often considered agricultural waste, is a valuable source of bioactive antibacterial agents. The strong in vitro activity combined with promising in silico binding results highlights its potential in developing novel treatments, particularly against Gram-negative pathogens